Gastrointestinal Stromal Tumor with Repeated Multiple Cerebral Infarction Mimicking Ovarian Cancer with Trousseau's Syndrome - Misa Kobayashi; Yoshirou Otsuki; Hiroharu Kobayashi; Takashi Suzuki; Satoru Nakayama; Hiroshi Adachi (Hindawi Limited, 2022)
We report a case of gastrointestinal stromal tumor (GIST) with repeated multiple cerebral infarctions mimicking ovarian cancer. A 79-year-old postmenopausal woman had multiple cerebral infarctions with a giant pelvic tumor detected by computed tomography. Ovarian cancer with Trousseau's syndrome was suspected. Through laparoscopic biopsy on the tumor surface, she was diagnosed with left ovarian fibrosarcoma; although, the abdominal cavity could not be observed appropriately. Ovarian fibrosarcoma is an extremely rare tumor and still has no adequate treatment strategy. Complete resection was planned. The tumor was extremely fragile, and gelatinous that it easily bled. Meanwhile, the uterus and bilateral ovaries and fallopian tubes were all normal. The tumor invaded only the peritoneum near the left sacral uterine ligament and sigmoid colon, with no peritoneal dissemination. To completely remove the tumor, we performed total hysterectomy with bilateral salpingo-oophorectomy and omentectomy and sigmoidal and rectal resection with colostomy. Despite resuming her anticoagulant therapy on postoperative day 4, she had recurrent multiple strokes. On histopathological examination, tumor showed spindle cell proliferation with severe atypia, increased mitotic activity, and widespread necrosis. Immunohistochemical studies showed positive staining for c-kit, CD34, and DOG1. Thus, she was diagnosed with GIST. This case was rare and highly malignant, with a high risk of recurrence of GIST because of a giant ruptured tumor that had a mitotic activity of 36/10 high-power fields from the sigmoid colon. Multiple cerebral infarctions mimicking ovarian cancer recurred. Therefore, preoperative diagnosis of an atypical GIST was extremely difficult.